Development of Online-Based Learning Media with Massive Open Online Courses Method on Instructor Methodology Competency in the Directorate of Competency Standardization and Training Programs, Ministry of Manpower of the Republic of Indonesia - Herdiansyah Prayuda; Zainal Abidin Arief; Muktiono Waspodo (CV. Media Inti Teknologi, 2024)
This study aims for Vocational and Productivity Training Centers throughout Indonesia to implement the development of online-based learning media with the MOOC method on instructor methodology competency. This study integrates the Borg and Gall development method with ADDIE Learning Design. Data analysis uses qualitative and quantitative descriptive analysis. The results shown are the feasibility assessment by media experts obtained a score of 99.13%. The feasibility assessment by design experts obtained a score of 61.67% and the feasibility assessment by material experts obtained a score of 88.04%. Based on this assessment, it is considered feasible to use. The response of participants in the small group test was considered feasible with a score of 79.63%. In the large group trial, a score of 92.42% was shown which was categorized as very feasible. The effectiveness test was assessed by the test according to Donald Kick Patrick, namely the reaction level and learning level, the reaction level was tested with a cut-off point where the value was 96%, it can be seen that the value is above the cut-off point so that it can be categorized as very satisfied, thus the reaction test of this product is very effective. The learning level is calculated by looking at the significance between the values before and after the trial, the results show that the significance value is less than the specified value, which is at 0.001 <0.05 significance value so that there is a significant difference, thus this learning media can be categorized as effective.